Modeling habitat suitability of Hippophae rhamnoides L. using MaxEnt under climate change in China: A case study of H. r. sinensis and H. r. turkestanica - He, Xiao-hui; Si, Jian-hua; Zhu, Li; Zhou, Dong-meng; Zhao, Chun-yan; Jia, Bing; Wang, Chun-lin; Qin, Jie; Zhu, Xing-lin (Frontiers in Forests and Global Change, 2023)
Hippophaerhamnoides is widely known for its important ecological, economic, and social benefits. It is known as the pioneer plant of soil and water conservation, with homology in food and medicine. Here we used occurrence data and environmental (climate and soil) variables to simulate and predict the habitat distribution for H. r. sinensis and H. r. trkestanica in China, both at the current time and in the 2050s (2041-2060). ),Our aim was toand analyze the dominant factors effecting its distribution by using MaxEnt and the spatial analysis of geographic information system. The results indicated that the area of suitable habitat for H. r. sinensis is much larger than that of H. r. trkestanica in china. The suitable habitay of H. r. sinensis is concentrated in the middle and upper reaches of the Yellow River, mainly distributed in Shaanxi, Shanxi, Sichuan, Qinghai, Gansu, Ningxia, Tibet, and Inner Mongolia, and that of H. r. trkestanica is mainly distributed in Xinjiang and Tibet. and The former is mainly affected by bio13 (precipitation of the wettest month), bio11 (mean temperature of the coldest quarte) and bio3 (Isothermality),. The suitable habitat of H. r. trkestanica is mainly distributed in Xinjiang, and Tibet, and the latter is mainly affected by bio13 (precipitation of the wettest month), bio2 (mean di-urnal range) and bio15 (precipitation seasonality). ), and the former is also more stable in the face of future climate change. They are more susceptible to climate than soil in their survival. Although, the two subspecies tend to expand and migrate toward lower latitude under future climate scenarios, there are some differences. H. r. sinensis will migrate westward, while H. r. trkestanica will migrate eastward as a whole. They have a high stability of suitable habitat and are not at risk of extinction in the future. The study’s findings help to clarify the resource reserve of Hippophaerhamnoides L. in China, which will help to guide the protection of wild resources and to popularize artificial planting in suitable areas, and provides scientific basis for the protection of ecological environment.